A preparation method and application of nanocellulose

Through the combination of low-concentration organic acid catalysis and high-pressure homogenization, the problem of equipment corrosion and energy consumption in the preparation process of nanocellulose in the prior art is solved, and green and efficient nanocellulose production is achieved, providing New ideas for industrial application and improve the added value and application breadth of products.

CN116284459BActive Publication Date: 2025-01-17DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111490933.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-08
Publication Date
2025-01-17
Estimated Expiration
2041-12-08

AI Technical Summary

Technical Problem

Existing methods for preparing nanocellulose, such as inorganic acid hydrolysis and mechanical methods, have problems such as equipment corrosion, high energy consumption, and environmental pollution, making it difficult to achieve green and efficient industrial production.

Method used

Using low-concentration organic acid as a catalyst, combined with high-pressure homogenization technology, the cellulose raw material is hydrolyzed by controlling the solvent concentration, temperature, stirring speed and reaction time, and nanocellulose is further obtained through high-pressure homogenization treatment.

Benefits of technology

The high yield preparation of nanocellulose under low concentration organic acid catalysis is achieved, which reduces the risk of equipment corrosion, simplifies the process flow, improves energy utilization efficiency, provides an environmentally friendly production method, and the prepared nanocellulose size distribution is evenly distributed. , suitable for multiple application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application discloses a preparation method and application of nanocellulose. The preparation method comprises at least the following steps: mixing a cellulose raw material with an organic acid and water, reacting, and high-pressure homogenizing to obtain the nanocellulose. The cellulose raw material is selected from sawdust or agricultural waste; the sawdust is selected from at least one of poplar sawdust, beech sawdust or birch sawdust; the agricultural waste is selected from at least one of corn stalks or sugarcane bagasse. The present application adopts a method combining low-concentration organic acid catalysis with high-pressure homogenization to prepare nanocellulose. The process is simple and green, and the situation of excessive acid concentration corroding equipment in traditional inorganic acid preparation is avoided, providing a new idea for the industrial production of nanocellulose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a preparation method and application of nanocellulose, and belongs to the field of materials. Background Art

[0002] Cellulose is the most widely distributed renewable polymer in nature and is also the largest byproduct of its production process. Cellulose is widely found in plants, as well as in some animals and bacteria. Nanomaterials refer to materials in which at least one of the three dimensions is in the nanometer size (1-100nm). The size distribution of nanocellulose is closely related to the preparation process and the source of the cellulose. In recent years, the preparation of nanocellulose from renewable wood biomass has received a lot of attention. Nanocellulose has biodegradability, unique optical properties and anisotropy, as well as excellent mechanical properties and a large aspect ratio. These advantages can be used in paints, adhesives and coatings, as well as the oil and gas industry. It also has a wide range of potential applications in biomedicine, electronics, packaging, filtration, environmental protection and other fields.

[0003] The commonly used methods for preparing nanocellulose include inorganic acid hydrolysis and mechanical methods. The acid hydrolysis method often uses high-concentration inorganic acids, such as sulfuric acid and hydrochloric acid, which are easy to corrode equipment, and the resulting cellulose is prone to over-hydrolysis. The production process requires a large amount of water and is prone to produce a large amount of salt, which can easily cause irreversible damage to the environment. Mechanical methods include high-pressure homogenization, ball milling and other methods. The preparation process requires a large shear force to break the interaction between cellulose fibers, so it consumes a lot of energy. Summary of the invention

[0004] The cellulose raw material is hydrolyzed by using an organic acid solvent by controlling the solvent concentration, temperature, stirring speed and reaction time. During the acid-catalyzed reaction, the acidity of the organic acid solvent can initially decompose the cellulose pulp, and partially hydrolyze to obtain micro / nanocellulose. The hydrolyzate is diluted and then subjected to high-pressure homogenization. Under the action of strong shear stress, the fiber bundles are decomposed again to become nanocellulose.

[0005] The preparation of nanocellulose using organic acid catalysis combined with high-pressure homogenization is a green and simple preparation method that can prepare nanocellulose in high yield, providing a new idea for the industrial production of nanocellulose.

[0006] According to one aspect of the present application, a method for preparing nanocellulose is provided, comprising at least the following steps:

[0007] The cellulose raw material is mixed with an organic acid and water, reacted, diluted to obtain a mixed solution, and subjected to high pressure homogenization to obtain the nanocellulose.

[0008] The cellulose raw material is selected from wood chips or agricultural waste;

[0009] The sawdust is selected from at least one of poplar sawdust, beech sawdust or birch sawdust;

[0010] The agricultural waste is selected from at least one of corn stalks or sugarcane bagasse.

[0011] The organic acid is at least one selected from trifluoromethanesulfonic acid, trifluoromethanesulfonic acid, methanesulfonic acid, methanesulfonic acid, ethylsulfonic acid and p-toluenesulfonic acid.

[0012] The mass ratio of the cellulose raw material to the organic acid is 1:1-20;

[0013] The mass ratio of the organic acid to water is 0.05 to 1:1.

[0014] The reaction temperature is 50-150°C;

[0015] The reaction time is 1 to 40 hours;

[0016] The reaction is stirred; the stirring speed is 200-800 rpm.

[0017] The dilution is 1000 times of dilution with deionized water.

[0018] The temperature of the high pressure homogenization is 25-30°C;

[0019] The pressure of the high pressure homogenization is 500 to 1500 bar;

[0020] Optionally, the high pressure homogenization process is repeated 3 to 5 times.

[0021] According to another aspect of the present application, there is provided a nanocellulose prepared by the above-mentioned preparation method;

[0022] The diameter of the nanocellulose is 10 to 900 nm.

[0023] The beneficial effects of this application include:

[0024] 1) This application uses low-concentration organic acid as a catalyst, the hydrolysis reaction environment is less acidic, the requirements for equipment are relatively low, and it has good industrialization prospects.

[0025] 2) The process of the present application is simple and green, which improves the problem of high energy consumption in the traditional mechanical method of preparing nanocellulose.

[0026] 3) This application adopts a method combining low-concentration organic acid catalysis and high-pressure homogenization to prepare nanocellulose, which provides a new idea for the environmentally friendly nanocellulose production process.

[0027] 4) The nanocellulose prepared in the present application has uniform size distribution and is a high value-added product with a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1A and Figure 1B The SEM and TEM images of the #1 nanocellulose obtained in Example 1; Figure 1C is the statistical chart obtained according to 1B;

[0029] Figure 2A and Figure 2B The nanocellulose samples of the nanocellulose #1 obtained in Example 1 before and after being left to stand for one day;

[0030] Figure 3 X-ray diffraction analysis diagram of cellulose pulp and #1 nanocellulose obtained in Example 1;

[0031] Figure 4 FTIR measurements of cellulose pulp and #1 nanocellulose obtained in Example 1 are given. DETAILED DESCRIPTION

[0032] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0033] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0034] The yield is calculated as follows:

[0035] 1.0 g of beechwood cellulose pulp was subjected to hydrolysis reaction and high pressure homogenization to obtain a nanocellulose suspension. The suspension was centrifuged and the nanocellulose solid was freeze-dried and weighed. The mass was m n .

[0036]

[0037] The preparation method of cellulose pulp is as follows: strategy for generating high-quality cellulose and lignin simultaneously from woody biomass (X. Si, F. Lu, J. Chen, R. Lu, Q. Huang, H. Jiang, E. Taarning and J. Xu, Green Chem., 2017, DOI: 10.1039 / C7GC02492D.)

[0038] Example 1

[0039] Weigh 1.0g beechwood cellulose pulp and add it to a reactor, then add 20.0g of trifluoromethanesulfonic anhydride (1.0g) and water (19.0g), stir and mix and seal. Use nitrogen to replace the gas in the reactor, adjust the reactor temperature to 110°C, and the reaction time is 1200min. After the reaction, the reactor is allowed to stand at room temperature, and the reaction solution is centrifuged. The solid hydrolyzate is centrifuged and washed 3 times with deionized water to adjust the concentration to 0.1wt%. The suspension of the hydrolyzate is passed through a high-pressure homogenizer, and the pressure is adjusted to 1000bar. The homogenization number is 3 times, and nanocellulose is obtained, which is marked as #1 nanocellulose.

[0040] The prepared nanocellulose was labeled as sample #1, with a yield of 81.4% and a crystallinity of 84.3%.

[0041] #1 Electron microscopy test of nanocellulose

[0042] The SEM and TEM images of #1 nanocellulose are shown in Figure 1A and Figure 1B As shown, from Figure 1A It can be seen that the prepared nanocellulose is composed of nanofibers with uniform diameter. Figure 1B The obtained statistical graph Figure 1C It can be seen that the average diameter of nanocellulose is 27±8nm.

[0043] #1 Suspension test of nanocellulose

[0044] Depend on Figure 2A and Figure 2B It can be seen that the nanocellulose sample in Example 1 still has good suspension properties after being left to stand for one day.

[0045] #1 Crystallinity test of nanocellulose

[0046] Figure 3 X-ray diffraction analysis of the cellulose pulp and the nanocellulose in Example 1 is given, and the crystallinity of the nanocellulose in Example 1 is calculated to be 84% and the crystallinity of the cellulose raw material is 76% according to an empirical formula.

[0047] #1 FTIR Testing of Nanocellulose

[0048] Figure 4 The FTIR test of cellulose pulp and nanocellulose in Example 1 is given. Compared with the cellulose raw material, nanocellulose has no new characteristic peaks in the infrared spectrum, indicating that no new functional groups are formed.

[0049] Example 2

[0050] Weigh 0.5g beechwood cellulose pulp and add it to a reactor, then add 9.5g of trifluoromethanesulfonic acid (0.5g) and water (9.0g), stir and mix and seal. Use nitrogen to replace the gas in the reactor, adjust the reactor temperature to 120°C, and the reaction time is 1000min. After the reaction is completed, the reactor is allowed to stand at room temperature, and the reaction solution is centrifuged. The solid hydrolyzate is centrifuged and washed 3 times with deionized water to adjust the concentration to 0.1wt%. The suspension of the hydrolyzate is passed through a high-pressure homogenizer, and the pressure is adjusted to 900bar. The homogenization number is 3 times, and nanocellulose is obtained, which is marked as #1 nanocellulose.

[0051] The yield of the prepared nanocellulose was 80.2% and the crystallinity was 83.4%.

[0052] Example 3

[0053] Weigh 2.0g beechwood cellulose pulp and add it to a reactor, then add 34.0g of methanesulfonic anhydride (2.0g) and water (34.0g), stir and mix and seal. Use nitrogen to replace the gas in the reactor, adjust the reactor temperature to 100°C, and the reaction time is 800min. After the reaction is completed, the reactor is allowed to stand at room temperature, and the reaction solution is centrifuged. The solid hydrolyzate is centrifuged and washed 3 times with deionized water, and the concentration is adjusted to 0.1wt%. The suspension of the hydrolyzate is passed through a high-pressure homogenizer, and the pressure is adjusted to 800bar. The homogenization number is 3 times, and nanocellulose is obtained, which is marked as #1 nanocellulose.

[0054] The yield of the prepared nanocellulose was 80.7% and the crystallinity was 83.7%.

[0055] Example 4

[0056] 1.0g beechwood cellulose pulp was weighed and added to a reactor, and 17.0g of methylsulfonic acid (1.0 g) and water (16.0g) were added, and the mixture was stirred and sealed. The gas in the reactor was replaced with nitrogen, and the reactor temperature was adjusted to 90°C for 600min. After the reaction, the reactor was allowed to stand at room temperature, and the reaction solution was centrifuged. The solid hydrolyzate was washed 3 times with deionized water and the concentration was adjusted to 0.1 wt%. The suspension of the hydrolyzate was passed through a high-pressure homogenizer, and the pressure was adjusted to 1000 bar. The homogenization number was 3 times, and nanocellulose was obtained, which was marked as #1 nanocellulose.

[0057] The yield of the prepared nanocellulose was 81.1% and the crystallinity was 84.1%.

[0058] Example 5

[0059] Weigh 0.5g of beechwood cellulose pulp and add it to a reactor, then add 8.0g of p-toluenesulfonic acid (0.5g) and water (7.5g), stir and mix and seal. Use nitrogen to replace the gas in the reactor, adjust the reactor temperature to 80°C, and the reaction time is 400min. After the reaction, the reactor is allowed to stand at room temperature, the reaction solution is centrifuged, and the solid hydrolyzate is centrifuged and washed 3 times with deionized water to adjust the concentration to 0.1wt%. The suspension of the hydrolyzate is passed through a high-pressure homogenizer, the pressure is adjusted to 900bar, and the number of homogenizations is 3 times, that is, nanocellulose is obtained, which is marked as #1 nanocellulose.

[0060] The yield of the prepared nanocellulose was 80.2% and the crystallinity was 83.5%.

[0061] Example 6

[0062] Weigh 2.0g beechwood cellulose pulp and add it to a reactor, then add 30.0g of p-toluenesulfonic acid (2.0g) and water (28.0g), stir and mix and seal. Use nitrogen to replace the gas in the reactor, adjust the reactor temperature to 110°C, and the reaction time is 1200min. After the reaction, the reactor is allowed to stand at room temperature, and the reaction solution is centrifuged. The solid hydrolyzate is centrifuged and washed 3 times with deionized water, and the concentration is adjusted to 0.1wt%. The suspension of the hydrolyzate is passed through a high-pressure homogenizer, and the pressure is adjusted to 800bar. The homogenization number is 3 times, and nanocellulose is obtained, which is marked as #1 nanocellulose.

[0063] The yield of the prepared nanocellulose was 70.9% and the crystallinity was 83.1%.

[0064] Embodiments 7 to 30

[0065] The experimental steps of Example 7 are the same as those of Example 1, except that the cellulose raw material is changed to poplar cellulose pulp, the reaction time is changed to 1000 min, and the high-pressure homogenization pressure is changed to 800 bar.

[0066] The experimental steps of Example 8 are the same as those of Example 2, except that the cellulose raw material is changed to poplar cellulose pulp, the reaction time is changed to 800 min, and the high-pressure homogenization pressure is changed to 1000 bar.

[0067] The experimental steps of Example 9 are the same as those of Example 3, except that the cellulose raw material is changed to poplar cellulose pulp, the reaction time is changed to 600 min, and the high-pressure homogenization pressure is changed to 900 bar.

[0068] The experimental steps of Example 10 are the same as those of Example 4, except that the cellulose raw material is changed to poplar cellulose pulp, the reaction time is changed to 400 min, and the high-pressure homogenization pressure is changed to 800 bar.

[0069] The experimental steps of Example 11 are the same as those of Example 5, except that the cellulose raw material is changed to poplar cellulose pulp, the reaction time is changed to 1200 min, and the high-pressure homogenization pressure is changed to 1000 bar.

[0070] The experimental steps of Example 12 are the same as those of Example 6, except that the cellulose raw material is changed to poplar cellulose pulp, the reaction time is changed to 1000 min, and the high-pressure homogenization pressure is changed to 900 bar.

[0071] The experimental steps of Example 13 are the same as those of Example 1, except that the cellulose raw material is changed to cellulose pulp of sugarcane, the reaction time is changed to 800 min, and the high-pressure homogenization pressure is changed to 900 bar.

[0072] The experimental steps of Example 14 are the same as those of Example 2, except that the cellulose raw material is changed to cellulose pulp of sugarcane, the reaction time is changed to 600 min, and the high-pressure homogenization pressure is changed to 800 bar.

[0073] The experimental steps of Example 15 are the same as those of Example 3, except that the cellulose raw material is changed to cellulose pulp of sugarcane, the reaction time is changed to 400 min, and the high-pressure homogenization pressure is changed to 1000 bar.

[0074] The experimental steps of Example 16 are the same as those of Example 4, except that the cellulose raw material is changed to cellulose pulp of sugarcane, the reaction time is changed to 1200 min, and the high-pressure homogenization pressure is changed to 900 bar.

[0075] The experimental steps of Example 17 are the same as those of Example 5, except that the cellulose raw material is changed to cellulose pulp of sugarcane, the reaction time is changed to 1000 min, and the high-pressure homogenization pressure is changed to 800 bar.

[0076] The experimental steps of Example 18 are the same as those of Example 6, except that the cellulose raw material is changed to cellulose pulp of sugarcane, the reaction time is changed to 800 min, and the high-pressure homogenization pressure is changed to 1000 bar.

[0077] The experimental steps of Example 19 are the same as those of Example 1, except that the cellulose raw material is changed to birch cellulose pulp and the reaction temperature is changed to 120°C.

[0078] The experimental steps of Example 20 are the same as those of Example 1, except that the cellulose raw material is changed to birch cellulose pulp and the reaction temperature is changed to 100°C.

[0079] The experimental steps of Example 21 are the same as those of Example 1, except that the cellulose raw material is changed to birch cellulose pulp and the reaction temperature is changed to 90°C.

[0080] The experimental steps of Example 22 are the same as those of Example 1, except that the cellulose raw material is changed to birch cellulose pulp and the reaction temperature is changed to 80°C.

[0081] The experimental steps of Example 23 are the same as those of Example 1, except that the cellulose raw material is changed to birch cellulose pulp and the reaction temperature is changed to 110°C.

[0082] The experimental steps of Example 24 are the same as those of Example 1, except that the cellulose raw material is changed to birch cellulose pulp and the reaction temperature is changed to 120°C.

[0083] The experimental steps of Example 25 are the same as those of Example 1, except that the cellulose raw material is changed to cellulose pulp of corn straw, the reaction temperature is changed to 100° C., and the homogenization pressure is changed to 900 bar.

[0084] The experimental steps of Example 26 are the same as those of Example 1, except that the cellulose raw material is changed to cellulose pulp of corn straw, the reaction temperature is changed to 90° C., and the homogenization pressure is changed to 800 bar.

[0085] The experimental steps of Example 27 are the same as those of Example 1, except that the cellulose raw material is changed to cellulose pulp of corn straw, the reaction temperature is changed to 80° C., and the homogenization pressure is changed to 1000 bar.

[0086] The experimental steps of Example 28 are the same as those of Example 1, except that the cellulose raw material is changed to cellulose pulp of corn straw, the reaction temperature is changed to 110° C., and the homogenization pressure is changed to 900 bar.

[0087] The experimental steps of Example 29 are the same as those of Example 1, except that the cellulose raw material is changed to cellulose pulp of corn straw, the reaction temperature is changed to 120° C., and the homogenization pressure is changed to 800 bar.

[0088] The experimental steps of Example 30 are the same as those of Example 1, except that the cellulose raw material is changed to cellulose pulp of corn straw, the reaction temperature is changed to 100° C., and the homogenization pressure is changed to 1000 bar.

[0089]

[0090]

[0091]

[0092] The nanocellulose obtained according to Examples 2 to 30 was tested and had similar properties to #1.

[0093] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing nanocellulose, characterized in that: At least the following steps are included: The cellulose raw material is mixed with an organic acid and water, reacted, diluted to obtain a mixed solution, and high pressure homogenized to obtain the nanocellulose; The organic acid is selected from at least one of trifluoromethanesulfonic acid, trifluoromethanesulfonic anhydride, methanesulfonic anhydride, methanesulfonic acid, ethylsulfonic acid and p-toluenesulfonic acid; The mass ratio of the organic acid to water is 0.05 to 1:

1.

2. The preparation method according to claim 1, characterized in that: The cellulose raw material is selected from wood chips or agricultural waste; The sawdust is selected from at least one of poplar sawdust, beech sawdust or birch sawdust; The agricultural waste is selected from at least one of corn stalks or sugarcane bagasse.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the cellulose raw material to the organic acid is 1:1-20.

4. The preparation method according to claim 1, characterized in that: The reaction temperature is 50-150°C; The reaction time is 1 to 40 hours; The reaction is stirred; the stirring speed is 200-800 rpm.

5. The preparation method according to claim 1, characterized in that: The dilution is 1000 times of dilution with deionized water.

6. The preparation method according to claim 1, characterized in that: The temperature of the high pressure homogenization is 25-30°C; The pressure of the high-pressure homogenization is 500-1500 bar.

7. The preparation method according to claim 1, characterized in that: The high pressure homogenization process is repeated 3 to 5 times.

8. A nanocellulose, characterized in that Prepared by the preparation method according to any one of claims 1 to 7; The diameter of the nanocellulose is 10 to 900 nm.